2017
DOI: 10.3201/eid2303.161499
|View full text |Cite
|
Sign up to set email alerts
|

Zika Virus RNA Replication and Persistence in Brain and Placental Tissue

Abstract: Zika virus is causally linked with congenital microcephaly and may be associated with pregnancy loss. However, the mechanisms of Zika virus intrauterine transmission and replication and its tropism and persistence in tissues are poorly understood. We tested tissues from 52 case-patients: 8 infants with microcephaly who died and 44 women suspected of being infected with Zika virus during pregnancy. By reverse transcription PCR, tissues from 32 (62%) case-patients (brains from 8 infants with microcephaly and pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
194
1
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 189 publications
(208 citation statements)
references
References 39 publications
11
194
1
2
Order By: Relevance
“…Such clinical signs and behavioral abnormalities can be partially associated with altered glucocorticoid levels [7]. Zika virus also replicates in the placenta [8][9][10], a crucial player in cortisol traffic from mother to fetus in humans [11] and pigs [12]. Thus, we hypothesize that congenital ZIKV infection may affect in utero cortisol levels.…”
mentioning
confidence: 97%
“…Such clinical signs and behavioral abnormalities can be partially associated with altered glucocorticoid levels [7]. Zika virus also replicates in the placenta [8][9][10], a crucial player in cortisol traffic from mother to fetus in humans [11] and pigs [12]. Thus, we hypothesize that congenital ZIKV infection may affect in utero cortisol levels.…”
mentioning
confidence: 97%
“…More recently, data from several epidemiological [5,6] and preclinical [7][8][9] research studies supported this idea, presenting direct evidences for the association between Zika virus infection and fetal disorders, including microcephaly. In a study led in Rio de Janeiro, Brazil, fetal analysis by ultrasonography of 42 infected pregnant women showed that 12 presented fetal abnormalities (29%).…”
Section: Zika Virus Infection and Neuronal Disordersmentioning
confidence: 92%
“…For example, more extended periods of viremia have been observed in pregnant women and fetuses 85 , and ZIKV RNA was detected throughout the mother and the fetus in animal models 8688 . Immune responses of pregnant monkeys and mice infected with ZIKV appear similar compared to non-pregnant infected animals 87,89 .…”
Section: Protection In Pregnancymentioning
confidence: 99%